Implementation of Sharia Principles in Online Buying and Selling Practices in Indonesia - Asiah, Nur; Abidin, Zaenal (Zabags Qu Publish, 2024)
The practice of online buying and selling in Indonesia is increasingly growing along with advancements in digital technology. However, it is crucial to ensure that these transactions align with Sharia principles, particularly in a predominantly Muslim society. This study aims to analyze the implementation of Sharia principles in online trading practices in Indonesia, focusing on aspects of justice, honesty, and transparency. The research method employed is a qualitative approach with data collection techniques through literature reviews and in-depth interviews with Sharia business practitioners and Muslim consumers. The research findings indicate that most e-commerce platforms in Indonesia have adopted Sharia principles, although challenges remain in implementation, particularly regarding misleading advertisements and usurious transactions. The study concludes that strengthening regulations and providing education to consumers and business actors are necessary to ensure compliance with Sharia principles in online transactions. The implications of these findings suggest that the government and relevant institutions need to enhance oversight of online trading practices to prevent violations of Sharia principles. Additionally, e-commerce entrepreneurs are encouraged to provide educational features that help consumers select products and conduct transactions in accordance with Islamic values.